Tracing the Story of Food Across Food Systems - Khan, Sabiha Ahmad (Frontiers in Communication, 2022)
This paper addresses the impulse to render systemic food systems issues into stories in light of ongoing challenges such as food scares, food fraud, and the COVID-19 pandemic. Such stories about food systems are seen as embodying the ideal of supply chain transparency currently in vogue and regarded as key to solving food system inequities by shedding light on them. Read in the context of documentary cinematic unveilings of unethical production practices, transparency initiatives of various types, particularly those dependent on the real-time, crypto-ensured storytelling of blockchain and digital twinning technology, would seem to provide a new model of indexicality, a new contract with social reality. However, such tracing systems and the questions they raise instead describe the way in which food—and the land, people and animals who are involved in its production—becomes fodder for various power plays.